Role of the capsule and the O antigen in resistance of O18:K1 Escherichia coli to complement-mediated killing. - Pluschke, G (1983)
Epidemiological data show that O18:K1 Escherichia coli is a common cause of neonatal bacteremia and meningitis. These bacteria were capable of multiplying in the bloodstream of newborn rats and were resistant to the bactericidal effects of complement in the absence of specific antibodies. The roles played by the O antigen and the K antigen in complement resistance were analyzed by comparing the bactericidal effects of normal sera and of sera deficient in various complement components or in immunoglobulins. These sera were tested on O18:K1 bacteria and on mutants lacking either the lipopolysaccharide O antigen or the K1 capsular polysaccharide. In addition, O1:K1 cells, which can cause pyelonephritis but which are rare in newborn meningitis and which do not multiply in the bloodstream of newborn rats, were also examined. Different mechanisms of protection against the alternative and classical pathways were recognized: K1-positive cells were resistant to the bactericidal activity of sera deficient in classical complement pathway components, whereas K1-negative cells were sensitive to these sera. Based on these results and on those from complement fixation assays, the K1 sialic acid polysaccharide impedes the activation of, and thus protects the bacteria against, the alternative complement pathway. Not only the K1-negative mutant cells but also O1:K1 bacteria and mutants lacking the O18 oligosaccharide repeating units of the lipopolysaccharide were sensitive to the classical complement pathway. These bactericidal effects were observed even in the absence of specific antibodies. It is proposed that both the K1 capsule and the O18 oligosaccharide restrict antibody-independent classical pathway activation by shielding deeper structures on the cell membrane that are capable of activating this pathway.